Laparoscopic management of congenital mesoblastic nephroma- case report - Anakievski, D. (Urol Case Rep, 2019)
Congenital mesoblastic nephroma (CMN) also called leimyomatous harmartoma is a mesenchymal renal tumor. CMN is the most common solid tumor in newborns and young infants which is basically benign. Pathologically there are three variants of CMN - classic (conventional), cellular (which is more aggressive) and mixed. In a complete surgical removal of the tumor (nephrectomy), the literature results are excellent.